In a Kafkaesque catacomb: The killing of Ihor Homenyuk by the Portuguese customs and immigration bureaucracy - Cunha, M. P.; Rego, J.; Clegg, S.; Giustiniano, L. (Journal of Political Power, 2023)
Bureaucracies, especially state bureaucracies, are typified as rational-legal organizations. We study how one such bureaucracy acted as neither rational nor legal but proved to be a space of exclusion. Ihor Homenuyk, a Ukrainian citizen, was ‘retained’ and then killed by the Portuguese foreigners and borders service. Police abuse has been much in the news in recent times, as a result of the Black Lives Matter movement. The issues are wider than those of racial injustice, however; they go to the nub of what it means to protect both the citizen and the honour of these organizations that engage with them in a way that is required to be legally rational. We use the case to open the black box of abuse and advance an explanation of how vicious dynamics happen.